Evaluación del desempeño de una red de datos corporativa - Betancourt Uscátegui, Alvaro; Mendez G, Harol (Ingeniería, 2008)
Performance evaluation in telecomunication networks is important for the management, expansion and quality of service. The paper presents a metodology for the performance evaluation network data, but the same could be used for networks with other type of traffic.